4/5(y-1/9)=2/5(y+5)

Simple and best practice solution for 4/5(y-1/9)=2/5(y+5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4/5(y-1/9)=2/5(y+5) equation:


y in (-oo:+oo)

(4/5)*(y-(1/9)) = (2/5)*(y+5) // - (2/5)*(y+5)

(4/5)*(y-(1/9))-((2/5)*(y+5)) = 0

(4/5)*(y-1/9)+(-2/5)*(y+5) = 0

4/5*(y-1/9)-2/5*(y+5) = 0

4/5*(y-1/9)-2/5*(y+5) = 0

2/5*y-94/45 = 0

2/5*y-94/45 = 0

2/5*y-94/45 = 0 // + 94/45

2/5*y = 94/45 // : 2/5

y = 94/45/2/5

y = 47/9

y = 47/9

See similar equations:

| 6+9i=0 | | 8=3a-1 | | 4+8n=7n+3 | | -1.5w+4.2=-3.2w-2.6 | | 5(5x+9)=25x+45 | | 4n-7=5(2n+7) | | -4(6y-8)-y=-2(y-2) | | 2x-3=3(1-x) | | 950+700+5x=800+400+10x | | 7/8=y-1/6 | | x=60x+259240 | | 12+4(z-3)=-5z+5 | | 1.4(z+0.5)=0.7(z-13) | | 3/2c+4=15 | | 5x^2+28+15=0 | | (-20/30)27/30 | | -5x-19=-13 | | 5*3/4*1/3 | | 2x(-3)=6 | | 7b/4+5=54 | | 12-2(7+2t)=2(t-1) | | 5x^2=42x+27 | | 3y+x=-16 | | 3y+x=-16 | | (4x-5)/(3x+7) | | 4(4-8y)-y=3y+7 | | 2/3c+4=15 | | f(x)=-3 | | 8=3c-7 | | 3x+1/4=4x+3/4 | | 2x^2-27x+168=0 | | 3y+14=5y |

Equations solver categories